The value of prednisolone acetate provocative test before intravitreal triamcinolone acetonide injections. Issue 4 (July 2020) - Saady, Aya Mohammed; Fouad, Heba M; Abdullatif, Abdussalam M; Helmy, Youssef A H; Macky, Tamer A; Mansour, Khaled
Purpose: The aim of this study was to investigate the diagnostic value of a topical prednisolone acetate 1% provocative test for steroid-induced ocular hypertension before intravitreal triamcinolone acetonide injection. Methods: This is a prospective, single-center, randomized controlled study at Kasr El Aini Hospital, Cairo University. Patients scheduled for intravitreal triamcinolone acetonide were enrolled and randomly allocated in a ratio 2:1 to either Group A: received prednisolone acetate provocative test and those who did not develop SIOH proceeded with intravitreal triamcinolone acetonide or Group B: did not receive prednisolone acetate provocative test and proceeded directly to intravitreal triamcinolone acetonide. Intraocular pressures were measured weekly for 4 weeks following intravitreal triamcinolone acetonide. Steroid-induced ocular hypertension is defined as intraocular pressure increase of 5 mmHg or more from baseline after prednisolone acetate provocative test or intravitreal triamcinolone acetonide. Results: A total of 66 eyes (66 patients) were included. Of which, 10 eyes (23.8%) showed prednisolone acetate provocative test steroid-induced ocular hypertension during the 4-week period. Intravitreal triamcinolone acetonide steroid-induced ocular hypertension was less likely to develop in Group A (prednisolone acetate provocative test non-steroid-induced ocular hypertension, n = 32, 31.25%) than in group B (n = 24, 54.2%) (p = 0.006, odds ratio: 0.178, 95% CI: 0.53–0.596). Our test achieved a negative predictive value of 68.75%. Conclusion: The topical prednisolone acetate provocative test may be a useful method to predict a steroid-induced ocular hypertension following intravitreal triamcinolone acetonide.